Эффективность экологического контроля загрязнения производственных площадок нефтепродуктами - Уберман, В. И.; Васьковец, Людмила Антоновна (НТУ "ХПИ", 2006)
Розроблена система якісних критеріїв для оцінки ефективності дій при екологічному контролі забруднення земель виробничих майданчиків підприємств, яка перевірена на прикладі державного контролю виробничого майданчика підприємства ВАТ "Тепловозоремонтний завод", м. Полтава, для випадка пріоритетної забруднюючої речовини – нафтопродуктів. Критерії охоплюють усі ланки процедури контролю, від визначення еколого-правового статусу об'єкта до оцінки можливої шкоди від забруднення. Критерії пропонується використовувати в еколого-інспекторській діяльності, при проведенні науково-технічних, екологічних, судових експертиз та арбітражних дослідженнях умов екологічної безпеки.

The system of quality criteria for assessing the efficiency of environmental inspection of polluted soils within sites of industrial enterprises (plants) is proposed and examined. These criteria were used for the example of state inspection on industrial site of JSC "Heat-engine locomotive repairing plant" in Poltava city, for the case of oil products pollution, which are priority contaminants. These criteria describe and include all stages of inspection procedure, from determination of environmental law status for inspected site to possible harm (damage) caused by given pollution. These criteria proposed for usage in environmental inspection activity, as for different kinds of expertise: scientific and engineering, environmental, legislation expertise, and for arbitrage examinations.
Keywords: окружающая природная среда; агрохимикаты; грунтовые воды; отраслевые загрязнения; экологические правонарушения